A obrigatoriedade do ensino de filosofia e a formação de professores desta disciplina que atuam em uma região da grande São Paulo - Chagas, Rita de Cássia Alves das (2011)
It is intended to promote discussion that research on teacher education and its role in the discipline of philosophy, specifically in the public of the State of SP, with a focus on cities of Suzano and Ferraz de Vasconcelos, due to the inclusion of compulsory education philosophy at the high school curriculum, Law 11.684/2008 from a literature review on the historical process of the teaching of philosophy in Brazil and the theoretical foundation of Pierre Bourdieu - Post review - on cultural capital and conversion by analyzing the supply undergraduate courses in philosophy at the city of São Paulo, thus producing a comparison of academic versus professional performance.